Influence of various energy settings and overlap ratios on size and continuity of lesions in a laser balloon ablation in vitro model. (3rd July 2019) - Nagase, Takahiko; Asano, So; Yukino, Midori; Mori, Hitoshi; Goto, Koji; Ikeda, Yoshifumi; Iwanaga, Shiro; Muramatsu, Toshihiro; Mukaida, Hisamitsu; Kato, Ritsushi; Matsumoto, Kazuo
Abstract: Introduction: The influence of power (Watt [W]) and total energy (Joule [J]) on lesion size and the optimal overlap ratio remain unclear in laser balloon (LB) ablation for atrial fibrillation. We aimed to evaluate lesion size and visible gaps after LB ablation with various energy settings and different overlap ratios in vitro model. Methods and Results: Chicken muscles were cauterized using the first‐generation LB with single applications of full and a half duration of six energy settings (5.5 W/30 seconds [165 J] to 12 W/20 seconds [240 J]) and varying power (5.5‐12 W) at the constant total energy (160 J). Three overlapped ablations with different ratios (25% and 50%) for each energy setting were also performed to evaluate the visible gap degree categorized from 1 (perfect) to 3 (poor). Twenty lesions were evaluated for each energy setting. In single applications of full duration, lesion depth, lesion volume, and maximum lesion diameter increased according to the total energy (all, P  <   .001) and were greater than in those of half duration in each energy setting (all, P  <   .05). However, applications with larger power created larger lesion volume and maximum lesion diameter at constant total energy ( P  <   .05). The visible gap degree was better in all energy settings with 50% overlapped ablation than in those with 25% (all, P  <   .001). Conclusion: Lesion size depends not only on power but also on total energy in the LB ablation. Sufficiently overlapped ablations allow continuous lesion formation.